Sustainability in design projects : a proposal to apply sustainability to education and professional practice - Pedro, Josélia (2022)
Higher education institutions have a responsibility to contribute to a more sustainable development. However, this contribution hasn’t always been consequential, especially when the focus is more on the construction of mere tools for sustainability, than on the process of internal transformation. That is, on the development of a true training for sustainability, consequently for a curriculum more oriented towards sustainability and with valid contributions for sustainable development, namely in the regions where they are based. On the other hand, ecodesign analysis tools, namely checklists, have been used successfully in companies, but also in education, and have made an important contribution to sustainability, fundamentally in the environmental and economic dimensions. Consolidated experiences in these areas have shown that employing these tools implies a contextualization of their use, in the case of their application in a teaching context, among students, or in a business environment, among professionals. It depends on the social, economic, and business context of the region or country, but, in the specific case of an application in education, it also depends on the type of subjects and the teaching and learning methods. In addition, the usefulness of the checklists is observed in various contexts of everyday life, but also in the professional environment and in teaching, as it is a tool that can help teachers and students to guide projects towards the final objectives, also valuing the process of getting there. The present study emerged from an investigation carried out within the scope of sus- tainability in communication design projects, involving several curricular units of a communication design course. Its final objective is to formulate a proposal for the application of sustainability to education and professional practice in this field of design. The main intention is to encourage design practices that consider aspects of environmental, social and economic sustainability, consolidating the training of students for a more sustainable development. At the methodological level, the study was grouped into four phases of action. In the first phase, the state of the art was analysed, the most appropriate method was chosen – an Ecodesign Checklist – and developed to evaluate communication design projects and to introduce improvements in products sustainability and design projects. Three curricular units from the third year of the Communication Design bachelor’s degree were selected, which allowed to carry out the communication design project (Communication Design IV subject), create ecodesign strategies (Sustainable Design subject) and plan their graphic production (Graphic Production I subject). Within this context a packaging and labelling design problem was defined as the project to be carried out evolving the subjects, having in mind the region where the school is located. To this end, an Ecodesign Checklist for Packaging and Labelling was developed, which allowed the design aspects for sustainability to be articulated between the three curricular units. In a second methodological phase, the Packaging and Labelling Ecodesign Checklist, was implemented and a first assessment study was carried out, regarding the potential contributions to the main aspects of sustainable development and to the training and curriculum of students involved. In addition to put in practice the Packaging and Labelling Ecodesign Checklist, surveys were also carried out with the involved students, in order to assess the impact of using the method on their curricular training and on their design practices. It is expected that in a third phase, this study can be applied to other subjects of the Communication Design degree and in a fourth phase to be extended to professional practice.reflections obtained in the first two methodological phases of this investigation, evaluating the importance of conducting the inquiry into a more holistic perspective, which includes a curriculum and training for sustainability, transposing the limits of the design project or of the designed products. It is also presented here the study contributions evaluation, specifically the Ecodesign Checklist for Packaging and Labelling, for the “Sustainable Development Goals - 2030” in Portugal and in the region where the higher education institution is located, highlighting the aspects considered as fundamental, and within the reach of design and communication designers. The first presented results are exploratory, as the intention is to develop the study by comparing results on a continuous basis. The evaluation of the Packaging and Labelling Ecodesign Checklist was carried out considering the academic universe in which it was implemented and intends to establish improvement parameters for its use. These parameters include the ease of use of the Checklist; the achievement of ecodesign objectives and of social and economic sustainability; and the contribution to students' training in the scope of sustainability. Some of the criteria initially defined for this study, specifically criteria related to collaborative practices applied to the field of design, were conditioned by the constraints of social confinement. However, it is expected to apply and test these criteria in the next round of the Ecodesign Checklist implementation. This article presents the first analyses and importance that this area of design has in